Letting Bodies be Bodies: Exploring Relaxed Performance in the Canadian Performance Landscape - LaMarre A; Rice C; Besse K (Brock University Press, 2021)
There is an increasing movement toward accessibility in arts spaces, including recent legislative changes and commitments at individual, organizational, and systemic levels to integrating access into the arts across Canada. In this article, we explore Relaxed Performance (RP) in the context of this movement. We present the results of a reflexive thematic analysis of interviews conducted with participants who completed RP training offered by the British Council to . understand the training’s effectiveness and impact. We explore the significance of the training, and of RP in general, and in relation to disability studies and cultural and political activism. We undertake this exploration against a backdrop of interrogating who RP is for and by. The themes we describe are: Committed to Access, Training is Critical, Inviting Bodies to be Bodies, and Imagining Audiences. These themes tell a story of how RP relates to broader access work, the importance of training grounded in and led by disability/difference, the need to consider the relationships between bodies and spaces, and the tensions inherent to billing RP as “for all.” We conclude with an exploration of possible modifications, enhancements, or theoretical imaginings that could help RP to become more radically open to difference as it emerges, shifts, and changes.